Simultaneous Incidental Parathyroid Carcinoma and Intrathyroid Parathyroid Gland in Suspected Renal Failure Induced Hyperparathyroidism - Pappa, Andrew; Hackman, Trevor (The Surgery Journal, 2017)
Hyperparathyroidism is a common disorder affecting more than hundreds of thousands of people annually. While most commonly secondary to an adenoma, it may also arise from four-gland hyperplasia or malignancy. In the case of primary hyperparathyroidism, the number of glands involved may be unknown prior to surgery. In contrast, the metabolic disorder associated with renal failure induced hyperparathyroidism ensures a hyperplasia picture. Despite the uniform hyperplasia seen in tertiary disease and the preoperative expectation for four-gland exploration, our case demonstrates the continued need for a surgeon's vigilance during dissection to identify all glands and appropriately use intraoperative parathyroid hormone (PTH) testing. In addition, while intraoperative PTH assessment is an effective method for confirming adequacy of treatment for hyperparathyroidism, only surgical pathology can confirm malignancy, which should be considered with PTH levels > 1,000. The case also underscores the importance of comprehensive surgery management and mindful interpretation of intraoperative PTH levels in the management of hyperparathyroidism. Standard surgical technique includes complete exploration of the central compartment, and thyroid lobectomy when the aforementioned exploration fails to reveal the necessary parathyroid tissue, especially with a persistently elevated PTH. Without a standardized progressive compartment exploration and judicious use of intraoperative hormone testing, intrathyroidal parathyroid glands can be missed.
Keywords: tertiary hyperparathyroidism; parathyroid cancer; intrathryoidal parathyroid; intraoperative PTH; parathyroidectomy